Probabilistic automata and stochastic languages - Soh, Royson Jun Heng (Nanyang Technological University, 2024)
This paper explores into probabilistic automata and stochastic languages, which serves as an overview to its concepts. Probabilistic Automata, which is a generalisation of nondeterministic finite automata, will be the main focus in this paper. We shall study the mathematical foundations, concepts and properties of Probabilisitic Automata and the languages recognised by these automata. We will also study the link between finite automata and probabilistic automata, and see some applications.